Effect of Virechana on CRP in a Patient of Metabolic Syndrome (International Journal of Ayurveda and Pharma Research, 2024)
Metabolic Syndrome is a result of metabolic impairment involving multiple systemic manifestations. Over nourishment, deposition of visceral fat, physical inactivity, sedentary lifestyle, genetic predisposition, familial tendency, mismanagement of physical or mental stress, irregular sleep- wake cycle, etc. These metabolic errors are actually resulted by indulging in the etiological factors that cause Medodushti in turn leading to Medoroga. Such etiological factors are called as Santarpana karaka Nidanas which include the food articles that are rich in Snigdhamsha, Madhura rasa, Guru and Pichchila gunas and also the activities that favour excessive nourishment and deposition of Meda Dhatu. This abnormally nourished Medo dhatu will contain Ama which further damages to manifest into metabolic syndrome. Virechana is a type of Shodhana Karma – Biopurification process that is potent enough to cleanse the channels and bring vitality to the Dhatus in the body. It is said to be improving bioavailability of medicines by cleansing at intestinal level and also by enhancing the demand and supply mechanism at tissue level. By removing the debris and unwanted accumulations in the channels, Virechana acts as Sroto vishodhaka and Medo hara also. By removing excess Kledamsha from the body, it reduces oedema, inflammation and also improves tissue permeability. Aim: To assess the effect of Virechana in metabolic syndrome, dyslipidaemia. Methodology: Administration of Amapachana followed by Virechana karma. Result: There was marked improvement in signs, symptoms and biochemical parameters after intervention. Conclusion: Virechana is significantly effective on altered levels of lipids, elevated blood sugar level and also raised ESR.